The Effectiveness of Leaf Powders from Several Types of Plants as Botanical Insecticides Against Mung Bean Beetle Pest (Callosobruchus chinensis L.) in Storage - Prisilya Makuku; Muhammad R Uluputty; Jeffij V Hasinu (JURNAL BUDIDAYA PERTANIAN, 2022)
Mung bean (Vigna radiata L.) has the third economic value among the legume group in Indonesia, after soybeans and peanuts. In storage, mung beans are often attacked by the beetle pest Callosobruchus chinensis L.; thus, it is necessary to control these pests. One way to control it is by using botanical insecticides derived from several types of plants, including lime leaf powder, noni leaf powder, nutmeg leaf powder, and lemongrass leaf powder. The purpose of this study was to obtain the most effective type of plant powder in controlling C. chinensis pests on mung bean seeds in storage. The study was conducted at the Plant Pest Laboratory of the Faculty of Agriculture, Pattimura University, which took place from November 2020 to January 2021. The study was conducted using a Completely Randomized Design with 4 treatments, namely DJ (15 g of lime leaf powder per 100 g of mung bean seeds), DM (15 g of noni leaf powder per 100 g of green bean seeds), DP (15 g of nutmeg leaf powder per 100 g of green bean seeds), DS (15 g of lemongrass leaf powder per 100 g of green bean seeds) and K (control, without leaf powder). Twenty imagos of C. chinensis were used in each treatment, and the experiment had 3 replicates. The variables observed included the initial symptoms after treatment, the mortality rate of the test insects, and the mortality of the test insects. The results showed that the DS (lemongrass leaf powder) and DM (noni leaf powder) treatments resulted in the mortality of the test insects of 93.33% and 91.67%, respectively, and were more effective than the other two treatments, namely DP (nutmeg leaf powder) and DJ (lime leaf powder) as well as controls.